Problema Tugas Terkembangan Remaja pada siswa - Yuhendra, Depi; Fitriani, Wahidah (Asosiasi Asesmen Pendidikan, 2025)
The background of this research is that adolescents find it difficult to accept physical and psychological conditions at the stage of their development, because in childhood they have used the concept of self-appearance and ways to improve self-appearance so that it is more in line with what one aspires to be. The problem with this research is that early school-age adolescents still need guidance and development to find out the developmental tasks at their age, because in adolescence the physical, emotional and intellectual condition of adolescents can go through a developmental task crisis. physical growth, and psychology, the purpose of this research is to describe the developmental task problems experienced by students in the aspect of achieving socially responsible behavior, achieving emotional independence, achieving good relationships with both sexes, being able to accept physical conditions and use them optimally. effective and capable of developing the intellectual skills and concepts necessary for citizens. To find out this, the author uses qualitative research that describes what is about the problem. Data collection was carried out through inventory in the form of questionnaires to students. These observations were made on the tasks of early adolescent development. Based on the results of the research that has been done, it can be concluded that the developmental problems that are often experienced by adolescents are the problem of having a desire and responsibility for social behavior, namely ethics and techniques of getting along and giving respect to others, being less open to others, feeling insecure when talking to others, unable to express opinions, dislikes being criticized for actions and opinions, does not know how to spend money properly. In the problem of emotional independence, namely irritability and unable to control emotions, worry about families who are less warm or less pleasant, often feel sad, afraid to try something new, sometimes brave, shy and easily confused about something.